Development of a CNN based robot vision system - Kui, Kenneth Wen Jun (Nanyang Technological University, 2023)
This final year project report presents the development and implementation of an object detection system using YOLOv5-obb, designed for detecting oriented bounding boxes (OBBs), and its integration with a UR5e (Universal Robots) robotic arm. The primary objective of this study is to detect cups using OBBs, label them according to their oriented positions, and manipulate the robotic arm to pick up a cup, move to another cup, and pour the contents accordingly.